2009
DOI: 10.1002/jmv.21582
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epidemiological features of GIIb norovirus outbreaks in Victoria, Australia, 2002–2005

Abstract: The epidemiology of GIIb norovirus outbreaks and the characteristics of GIIb open reading frame (ORF) 2 recombinant forms are poorly understood and this study examined these questions using norovirus-associated gastroenteritis outbreaks in Victoria, Australia, during 2002-2005. Twenty-one GIIb outbreaks were detected and were the second most common ORF 1 norovirus outbreak genotype (5%) after GII.4 (90%). Both GIIb and GII.4 outbreaks peaked in warmer months of the year but their periodicity was different. ORF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…Since a correlation was established between the complete nucleotide sequence of VP1 and a partial nt sequence (region D) (Vinjé et al 2004), this region has been used to genotype NoV. The comparison of different strains has been hampered by the use of different approaches for molecular characterization of NoV (Victoria et al 2007, Ferreira et al 2008, Bruggink & Marshall 2009, Nataraju et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Since a correlation was established between the complete nucleotide sequence of VP1 and a partial nt sequence (region D) (Vinjé et al 2004), this region has been used to genotype NoV. The comparison of different strains has been hampered by the use of different approaches for molecular characterization of NoV (Victoria et al 2007, Ferreira et al 2008, Bruggink & Marshall 2009, Nataraju et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Evidence based on recombinants generated from a small, ssDNA virus, maize streak virus, demonstrated that fragments of genetic material only function optimally if they reside within genomes similar to those in which they evolved (Martin et al, 2005 , 2006). Later, GIIb recombinants were identified in a wide range of countries, indicating their widespread distribution across continents (Bruggink & Marshall, 2009;Fukuda et al, 2008;Gomes et al, 2007). It is possible that recombination was able to give rise to novel NoV strains capable of epidemic spread in human In vitro MNV recombination populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide sequencing was carried out for the products of the RT-PCR protocols 2, 3 and 4 essentially as given previously [26]. For protocol 2, a fragment of 195 bp corresponding to nucleotides 5,133-5,327 relative to the norovirus reference strain JX459908 was used.…”
Section: Figmentioning
confidence: 99%
“…Where the typing tool was unable to type the fragment, a BLAST search was performed and the closest match was put into the typing tool to identify the genotype. Phylogenetic trees were constructed using Phylip v3.68, essentially as described previously [26], to examine the clustering patterns of ORF 1 and ORF 2 fragments. …”
Section: Figmentioning
confidence: 99%